PROYEK FILM SEJARAH SMANSARA: PRAKTIK SOSIODRAMA UNTUK MENGEMBANGKAN KARAKTER PROFIL PELAJAR PANCASILA PESERTA DIDIK SMA NEGERI 1 JEPARA - Asyif Awaludin Romadhoni; Aman Aman (Jurnal Pendidikan Sejarah Indonesia, 2022)
The purpose of research is to explain the application of sociodrama with historical short films to develop the character of Pancasila Students of SMA Negeri 1 Jepara. The research method used quantitative method with pre-experimental approach by giving a questionnaire regarding Pancasila Student Profiles to students SMA Negeri 1 Jepara.The subject of research consist of 214 students from six classes. The results of research showed there is a significant effect between the application of sociodrama and the output of historical short films on the character development of the Pancasila Student Profile students of SMA Negeri 1 Jepara students. This is very relevant to various learning theories that are oriented to the development of students' skills. The finding of this study support the concept of teachers not only convey knowledge, but also must develop the abilities of students.Penelitian ini bertujuan untuk menjelaskan penerapan sosiodrama dengan luaran film pendek sejarah untuk mengembangkan karakter Profil Pelajar Pancasila peserta didik SMA Negeri 1 Jepara. Penelitian ini menggunakan metode kuantitatif pendekatan praeksperimen dengan memberikan angket mengenai Profil Pelajar Pancasila kepada peserta didik. Subjek penelitian terdiri atas 214 peserta didik dari enam kelas Hasil penelitian menunjukkan penerapan sosiodrama dengan luaran film pendek sejarah berpengaruh signifikan terhadap pengembangan karakter Profil Pelajar Pancasila bagi peserta didik SMA Negeri 1 Jepara. Hal tersebut sangat relevan dengan berbagai teori pembelajaran yang berorientasi pada pengembangan keterampilan peserta didik. Temuan penelitian ini mendukung konsep guru tidak hanya menyampaikan pengetahuan, tetapi juga harus mengembangkan kemampuan peserta didik.